EFFICACY OF NARINGIN IN PROTECTING CARDIAC H9C2 CELLS FROM HYPERGLYCEMIC DAMAGE: POTENTIAL IMPLICATIONS FOR DIABETIC CARDIOMYOPATHY TREATMENT - Amer Mahmood; Randa AL-Ibrahim; Mona Elsafadi; Manikandan Muthurangan; Abdul-Aziz Siyal; Randa Alfotawi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Diabetes mellitus (DM) represents a pressing public health challenge globally, with profound implications in both developed and developing nations. It stands as one of the most pervasive and severe chronic conditions worldwide. This study delves into the potential therapeutic effects of naringin on H9c2 cardiac cells subjected to elevated glucose levels, specifically exploring its viability as a treatment for diabetic cardiomyopathy. Methods: For our experiment, we prepared a final concentration of 80.0 μM of NAR in distilled water, subsequently stored at 4.0°C. H9c2 cardiac cells, derived from embryonic rat ventricles, were cultured in DMEM supplemented with FBS, D-Glucose. In this study we simulated Diabetic Cardiomyopathy by exposing the cells to high D-Glucose concentrations. Viability was assessed using the AlamarBlue assay, while ROS production was detected using the DCFH–DA dye. RNA from treated and control cells was isolated to test different genes. Results and discussion: In summary, pre-treatment of H9c2 cardiomyocytes with 80.0 μM concentrations of both Naringenin and Naringin, prior to high glucose exposure, proved most effective, especially concerning the upregulation of the Bcl-2 anti-apoptotic gene. The present study explored the adverse impacts of high glucose (HG) on H9c2 cardiomyocyte cells, evidenced by symptoms like cytotoxicity, apoptosis, oxidative stress, and mitochondrial malfunctions, further underlined by a reduced cell viability. We discovered a pronounced linkage between the surge in reactive oxygen species (ROS) production and HG-driven cardiomyocyte damage. Conclusion: Naringenin (NAR) at 80.0 μM concentration, when pre-treated on H9c2 cardiomyocytes prior to high glucose exposure, effectively upregulates the Bcl-2 anti-apoptotic gene, offering protection against hyperglycemia-triggered cardiac damages by reducing ROS activity and cell apoptosis. The study reaffirms previous findings linking elevated HG levels to cardiomyocyte damage, emphasizing that an 80.0 μM NAR treatment for 2.0 hours is the most potent countermeasure against diabetic cardiomyopathy.